1979
DOI: 10.1017/s0022172400025730
|View full text |Cite
|
Sign up to set email alerts
|

Specific immunoglobulin responses after varicella and herpes zoster

Abstract: SUMMARYThe indirect immunofluorescence technique has been used to titrate the specific immunoglobulins in 200 sera from 64 patients with varicella, and 195 sera from 67 patients with herpes zoster. IgG and IgM antibodies were detected in all patients with varicella, and IgA in 59 (92 %). All three classes of antibody appeared 2-5 days after the onset of the rash, increased virtually simultaneously and reached maximum titres during the second and third weeks. IgG then declined slowly, but never became undetecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 47 publications
2
34
1
1
Order By: Relevance
“…In the present study VZV-IgM was detected in all 18 patients with varicella, in 7 of these (38-9 %) in the acute-phase serum obtained within a few days after onset of symptoms. This is in agreement with the results of others [2,4,8]. Furthermore, VZV-IgM was detected in serum from 13 out of 19 (68-4 %) patients with herpes zoster.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study VZV-IgM was detected in all 18 patients with varicella, in 7 of these (38-9 %) in the acute-phase serum obtained within a few days after onset of symptoms. This is in agreement with the results of others [2,4,8]. Furthermore, VZV-IgM was detected in serum from 13 out of 19 (68-4 %) patients with herpes zoster.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been obtained by others using both indirect assays as well as antibody-capture assays. In these reports VZV-IgM in patients with herpes zoster was detected by indirect radioimmunoassay in 69 % [4], by indirect immunofluorescense in between 50% and 78 % [1,2,8] and by AC-ELISA in between 50 % and 84% [6,7] of patients. In all studies the VZV-IgM response in patients with herpes zoster was found to be of a lesser magnitude compared to the response in patients with varicella and to be relatively shortlived.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations